Marine Biopolymers for Transdermal Drug Delivery - Kumar M.; Jha A.; Mishra B. (My University, 2025)
The use of marine biopolymers for topical formulations is a promising strategy for effective transdermal drug delivery applications. Marine biopolymers have certain advantages over conventional polymers such as multifunctionality, natural abundance, cost-effectiveness, biodegradability, hydrophilicity, cytocompatibility, minimal toxicity, and biocompatibility with other excipients or therapeutics. Often, marine biopolymers have intrinsic biological activities such as anti-inflammatory, antimicrobial, antioxidant, and anticancer, which may enhance the efficacy of the primary therapeutic ingredient or drug. Moreover, marine biopolymers owing to their structural diversity allow for surface modification providing multifunctionality to the structure that responds to the external stimuli such as pH, temperature, and light. Due to these distinctive properties, marine biopolymers can be used effectively for the preparation of dermal drug carriers, such as hydrogels, scaffolds, film, nanoparticles and microparticles, or nanoparticle- or microparticle-loaded carriers, and for transdermal applications, such as wound dressings, anti-infectives, anti-cancer, and tissue regeneration. This chapter outlines the various marine biopolymers used as multifunctional excipients for transdermal drug delivery systems and their sources, properties, and extraction methods, as well as their role in the development of transdermal drug delivery systems, the mechanism of transdermal absorption, and specific applications. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.